Identités culturelles et démocratie - Michel Wieviorka (Cahiers des Amériques Latines)
The debate on the cultural identities can be considered by three main manners. The first one consists in examining sociologically the new push, or renewed, cultural identities, asking to be recognized in the public space, that is the era of new social movements (feminists, ecologists, regionalists, etc.). The second entrance to these debates consists in considering rather the way the political philosophy takes care of these questions and in fact one of its major subjects. Finally, the third possible entrance consists in examining the propositions of institutional treatment which were born, from the 1960s, in front of the push of cultural differences within certain countries, the word multiculturalism being imperative itself, often in a indistinct way, although it refers actually to the policies which take care of the collective identities to bring them cultural rights, and thus certain recognition, possibly associated to social measures. This article examines these three approaches and proposes an analysis of what are, today, the cultural identities.